2006
DOI: 10.1016/j.psyneuen.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Task engagement and the relationships between the error-related negativity, agreeableness, behavioral shame proneness and cortisol

Abstract: SummaryPrevious results suggest that both cortisol mobilization and the errorrelated negativity (ERN/Ne) reflect goal engagement, i.e. the mobilization and allocation of attentional and physiological resources. Personality measures of negative affectivity have been associated both to high cortisol levels and large ERN/Ne amplitudes. However, measures of positive social adaptation and agreeableness have also been related to high cortisol levels and large ERN/Ne amplitudes. We hypothesized that, as long as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 61 publications
(82 reference statements)
9
63
2
2
Order By: Relevance
“…Changes in the amplitude of the ERN to performance feedback have been related to changes in self-reported engagement during a task (Yeung, Holroyd, & Cohen, 2005). In previous studies, using a task that required continuous performance for a rather long period of time (2.5 h), we found that the amplitude of the ERN decreased during task performance (most dramatically within the first 30 min) but increased again after providing the subjects with an opportunity to win a monetary reward by performing well Tops et al, 2006). We suggested that this may reflect reduced intrinsic engagement while performing a monotonous (i.e., boring), fatiguing task, compensated by extrinsic engagement after the reward manipulation.…”
Section: Methods Subjectsmentioning
confidence: 70%
See 3 more Smart Citations
“…Changes in the amplitude of the ERN to performance feedback have been related to changes in self-reported engagement during a task (Yeung, Holroyd, & Cohen, 2005). In previous studies, using a task that required continuous performance for a rather long period of time (2.5 h), we found that the amplitude of the ERN decreased during task performance (most dramatically within the first 30 min) but increased again after providing the subjects with an opportunity to win a monetary reward by performing well Tops et al, 2006). We suggested that this may reflect reduced intrinsic engagement while performing a monotonous (i.e., boring), fatiguing task, compensated by extrinsic engagement after the reward manipulation.…”
Section: Methods Subjectsmentioning
confidence: 70%
“…Several studies have associated measures of punishment sensitivity or negative affectivity such as BIS and neuroticism with larger ERN amplitudes (e.g., Boksem, Tops, et al, 2006;Hajcak et al, 2004;Luu et al, 2000;Pailing & Segalowitz, 2004;Tops et al, 2006). Agreeableness and its strong correlate empathetic concern (see note 1) have also been related to larger ERN amplitudes (Larson, Fair, Good, & Baldwin, 2010;Santesso & Segalowitz, 2009;Tops et al, 2006). Larson et al also found a positive association between ERN amplitudes and scores of empathetic fantasy, a measure of absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, lower cortisol has been shown to be associated with disruptive behavior disorder in boys (Dorn et al, 2009), callousness in male adolescents (Loney, Butler, Lima, Counts, & Eckel, 2006), as well as aggressive behavior (Böhnke, Bertsch, Kruk, & Naumann, 2010;van der Meij et al, 2015) and psychopathic traits (Cima, Smeets, & Jelicic, 2008;Holi, Auvinen-Lintunen, Lindberg, Tani, & Virkkunen, 2006) in adults. With regard to prosocial and related behaviors, evidence is scarce but positive associations have been reported for cortisol and the personality trait agreeableness (Tops, Boksem, Wester, Lorist, & Meijman, 2006;Vickers, Hervig, Poth, & Hackney, 1995), social affiliative behavior in children (Tennes, Kreye, Avitable, & Wells, 1986), quality of social relationships in adolescent girls (Booth, Granger, & Shirtcliff, 2008), and relationship functioning in mothers (Adam & Gunnar, 2001). …”
Section: Introductionmentioning
confidence: 99%